Program Penguatan Literasi Visual dalam Pembelajaran Bahasa Indonesia melalui Komik Edukasi Anak di SDN Karundang 1 Kota Serang - Yoma Hatima; Lili Fajrudin; Reksa Adya Pribadi (Prodi PGSD Unsultra, 2025)
Visual literacy skills are one of the important aspects in supporting elementary school students' literacy skills, especially in learning Indonesian. However, most of the teaching materials are still dominated by conventional texts that are less interesting for students. This community service activity aims to improve students' visual literacy through the use of educational comic media for children in learning Indonesian. This program was implemented at SDN Karundang 1, Serang City and involved teachers and students in grades IV and V. The implementation method was carried out through stages of socialization, teacher training, comic-based learning assistance, and evaluation. The educational comics used contained short stories with interesting illustrations that contained character values ​​and Indonesian language learning topics according to the curriculum. The results of the activity showed an increase in student enthusiasm in participating in learning, an increase in the ability to understand the contents of the reading, and student creativity in responding to visual texts. Teachers also acknowledged the ease of delivering material through visual media. Thus, the use of educational comics has proven effective as a means of strengthening visual literacy in learning Indonesian at the elementary school level. This program is expected to be a model for strengthening visual literacy in other schools.